The Influence of Learning Styles, Learning Environment, Learning Facilities, and Learning Interest on the Academic Achievement of Class X E Students in Economics Thru Study Habits as an Intervening Variable - Salminar Sababalat; Citra Ramayani; Jimi Ronald (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the influence of learning styles, learning environment, learning facilities, and learning interest on students’ academic achievement through learning habits as an intervening variable. The research was conducted on class X E students of SMA Negeri 2 Sipora, Mentawai Islands Regency, with a population of 271 students and a sample of 136 students selected using proportional random sampling. The research method applied was quantitative with an associative approach. Data analysis techniques included descriptive analysis and path analysis using IBM SPSS Statistics 22. The findings revealed that: (1) learning styles had no significant effect on learning habits; (2) the learning environment had a significant effect on learning habits; (3) learning facilities had no significant effect on learning habits; (4) learning interest had no significant effect on learning habits; (5) learning styles had no significant effect on academic achievement; (6) learning habits had no significant effect on academic achievement; (7) the learning environment had no significant effect on academic achievement; (8) learning facilities had no significant effect on academic achievement; and (9) learning interest had no significant effect on academic achievement.